SAILING STORIES - Rina Juwita; Mardliya Pratiwi Zamruddin; Ainun Nimatu Rohmah; Mohammad Fauzan Noor; Ahmad Hidayah (Universitas Nusa Cendana, 2026)
The study aims to explore the public relations (PR) practices employed to push forward maritime cultural tourism along the coast of East Kalimantan, specifically Berau Regency and the Derawan Islands. Given the modern digital age, there is the need to infuse local stories to support strategic public relations practices toward building destination identities and maximizing visitor’s enjoyment. This study applies the qualitative case study method using thorough interviews, participant observation, and analysis of promotional documents circulated by tourism authorities, businesses, and local residents. The findings highlight the use of public relations practices focusing on maritime stories -spread through social media portals, documentary screening, and community programs- having significantly promoted both destination exposure and attractivess. However, there are challenges related to narrative consistency, meaningful local outreach engagement, and enhancing stakeholder collaboration.